Cerebral oxygenation with different nasal continuous positive airway pressure levels in preterm infants. Issue 2 (21st October 2014) - Bembich, Stefano; Travan, Laura; Cont, Gabriele; Bua, Jenny; Strajn, Tamara; Demarini, Sergio
Abstract : Objectives: This study evaluates the effect of varying nasal continuous positive airway pressure (NCPAP) level on cerebral blood flow (CBF) and oxygenation in preterm infants. Methods: Oxy-haemoglobin (HbO2 ) and total haemoglobin (HbTot), as CBF estimates, and the ratio between HbO2 and HbTot (HbO2 /HbTot), as cerebral oxygenation estimate, were assessed by near-infrared spectroscopy in 26 stable preterm newborns at a postmenstrual age between 26 and 33 weeks. Baseline HbO2, HbTot and HbO2 /HbTot values were initially collected with NCPAP at 5 cm H2 O and then compared with values obtained with NCPAP levels at both 3 and 8 cm H2 O. Results: Compared with 5 cm H2 O, cerebral HbO2, HbTot and HbO2 /HbTot remained unchanged both after increasing (to 8 cm H2 O) and decreasing (to 3 cm H2 O) the NCPAP level. This result was observed both in regional areas (24 sites) and in the overall monitored area (frontal and parietal cortex). Compared with 8 cm H2 O, peripheral oxygen saturation significantly decreased at 3 cm H2 O (p=0.021). Heart rate did not change. Conclusions: No differences in CBF and cerebral oxygenation were observed with NCPAP levels in the range 3–8 cm H2 O despite a decrease in peripheral oxygenation with 3 cm H2 O.